Effective Photosensitization in Excited‐State Equilibrium: Brilliant Luminescence of TbIII Coordination Polymers Through Ancillary Ligand Modifications. Issue 10 (13th July 2022) - Kitagawa, Yuichi; Moriake, Ryoma; Akama, Tomoko; Saito, Koki; Aikawa, Kota; Shoji, Sunao; Fushimi, Koji; Kobayashi, Masato; Taketsugu, Tetsuya; Hasegawa, Yasuchika
Abstract: Molecular photosensitizers provide efficient light‐absorbing abilities for photo‐functional materials. Herein, effective photosensitization in excited‐state equilibrium is demonstrated using five Tb III coordination polymers. The coordination polymers are composed of Tb III ions (emission center), hexafluoroacetylacetonato (photosensitizer ligands), and phosphine oxide‐based bridges (ancillary ligands). The two types of ligand combinations induces a rigid coordination structure via intermolecular interactions, resulting in high thermal stability (with decomposition temperatures above 300 °C). Excited‐triplet‐state lifetimes of photosensitizer ligands (τ=120–1320 μs) are strongly dependent on the structure of the ancillary ligands. The photosensitizer with a long excited‐triplet‐state lifetime (τ≥1120 μs) controls the excited state equilibrium between the photosensitizer and Tb III, allowing the construction of Tb III coordination polymer with high Tb III emission quantum yield (≥70 %). Abstract : Molecular photosensitizers exhibit efficient light‐absorbing capabilities in photo‐functional materials. This work reports effective photosensitization at excited‐state equilibrium using Tb III coordination polymers. The coordination polymers are composed of Tb III ions (as emission centers), hexafluoroacetylacetonato (as a photosensitizer ligand), and phosphine oxide‐based bridges (as ancillary ligands). The ancillary ligand controls the excited state equilibrium between the photosensitizer and Tb III, allowing the construction of Tb III coordination polymer with high Tb III emission quantum yield (≥70 %).